2016
DOI: 10.1177/2057158516668081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an education intervention on nursing diagnoses in free-text format in electronic health records: A pretest–posttest study in a medical department at a university hospital

Abstract: Discussions on how nursing documentation should be carried out have been ongoing for the last decade. In this study, free-text format for nursing diagnoses was introduced to nursing staff at a university hospital in Norway. The aim of the study was to investigate the impact of an education intervention introducing nursing diagnoses in a free-text format following a problemetiology-symptom structure. A pretest-posttest design was performed to assess changes in quality and quantity in the nursing documentation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
0
16
1
4
Order By: Relevance
“…This is because these unexpected findings also confirm the poor education, lack of training of nurses and insufficient knowledge of the nursing process including nursing diagnosis. Previous studies revealed that educational programmes directed at improving diagnostic reasoning skills significantly increase the prevalence and accuracy of documented nursing diagnoses (Bruylands et al., ; Nøst, Frigstad, & André, ). In addition, lack of follow‐up and periodic auditing of nursing documentation records from the quality department might not only initiate bad practice and poor content by nurses’ documentation, but it also reflects the looseness and weakness of the quality assurance and monitoring system of the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This is because these unexpected findings also confirm the poor education, lack of training of nurses and insufficient knowledge of the nursing process including nursing diagnosis. Previous studies revealed that educational programmes directed at improving diagnostic reasoning skills significantly increase the prevalence and accuracy of documented nursing diagnoses (Bruylands et al., ; Nøst, Frigstad, & André, ). In addition, lack of follow‐up and periodic auditing of nursing documentation records from the quality department might not only initiate bad practice and poor content by nurses’ documentation, but it also reflects the looseness and weakness of the quality assurance and monitoring system of the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The main difference between the activities for the patients after the implementation of JoLNH seems to be the documentation and systemization. To be able to ensure that every patient gets custom activities, systematic and documentation are important (41,42). When describing the challenges with JoLNH many informants mentioned the obligation of documentation of performed activities, and that this documentation should be done in a speci c way.…”
Section: Discussionmentioning
confidence: 99%
“…Hemmati Maslakpak et al indicated that problembased documentation training increased the mean scores of nurses' reports (8). Nost et al (16) and Muller-Staub (20) found that educational interventions, such as problembased reporting methods, have significant effects on increasing the accuracy and reporting of nurses' diagnoses, interventions, and treatment outcomes and lead to the quality improvement of nursing reports. The results of a study by Abbaszadeh et al also showed a significant difference in the mean performance score of nurses in documentation between the pretest and posttest (14).…”
Section: Discussionmentioning
confidence: 99%